Systematic review on HIV situation in Addis Ababa, Ethiopia - Melaku Adal (BMC, 2019)
Abstract Background HIV prevalence in the Addis Ababa is still higher in key and priority populations. Therefore, this systematic review was carried out aiming in determining the prevalence of HIV and predisposing risk factors, identification of hotspot areas, key and priority populations, availability and utilization of services, and challenges and gaps to be addressed for prevention and control of HIV epidemic in Addis Ababa. Methods The documents relevant to address the objectives were collected from online databases Google scholar and PubMed for published works. In addition, unpublished survey and surveillance reports, performance reports and project assessment findings, and mapping results were collected from partner organizations working on HIV/AIDS prevention and control. Results It appears that the HIV prevalence stabilizes, but varies along areas and socio-demographic groups. The most common hot spots in Addis Ababa are areas where bars, groceries, pensions, guest houses, hotels, brothels, massage houses, khat houses, shisha houses, night clubs, drinking establishments and tourist frequented settings are concentrated. The recognized key population (KP) is the female sex workers (FSWs). There is sexual mixing of key and priority populations (KPPs) with the general population. There are various behavioural, biological and socio-economic predisposing risk factors that drive HIV epidemic, and respective behavioural, biomedical and structural intervention measures are identified in the presence of gaps and challenges to address the problem. Conclusions HIV prevalence in Addis Ababa seems stabilized. However, it varies along different groups of the population. There are many behavioural, biological and socio-economic factors that predisposed to HIV/AIDS. Weak monitoring of the quality of interventions, limited linkage of positive clients, lost to follow up, financial shortage, limited man-power and coordination, data quality and gaps in use of program data or research findings are some of the gaps and challenges. Therefore, prevention and control measures using behavioural, structural and biomedical interventions through filling of gaps and tackle challenges should be strengthened in order to prevent and control HIV transmission.